Utilization of Building Information Modelling Among Architects, Engineers and Contractors Towards Malaysia Construction Industry Performance: A Review - Razali, Farah Nadia; Md Anuar, Muhammad Haziq (Research in Management of Technology and Business, 2024)
Building Information Modelling (BIM) is a modelling technology that can assist with digital representation, design, project scheduling, cost, and time management. BIM enables the creation of 3D models that become a central location for stakeholders, especially the Architect, Engineer, and Contractor (AEC), to add or extract project data accurately, up-to-date, and accessible to the entire project team during design, construction, and operation stages. However, the implementation of BIM in Malaysia is still poor due to high adoption costs, complexity of advanced technology, and resistance to change for new technology. Nevertheless, BIM offers several benefits that can help boost construction performance. This study aims to analyse the integration of BIM into construction industry performance in Malaysia. The objective of this paper is to highlight the advantages of the utilization of BIM among AECs in Malaysia towards the performance of the construction industry. Previous studies based on the article journal and other secondary sources will be reviewed to gather the information. The review of this study will highlight the benefits of BIM among AEC in connection to construction industry performance. The review of this study will be significant in further research as it is beneficial to construction stakeholders, especially AEC.